Multivariate alterations in insula - Medial prefrontal cortex linked to genetics in 12q24 in schizophrenia. (December 2021) - Jiang, Wenhao; Rootes-Murdy, Kelly; Chen, Jiayu; Bizzozero, Nora I.Perrone-; Calhoun, Vince D.; van Erp, Theo G.M.; Ehrlich, Stefan; Agartz, Ingrid; Jönsson, Erik G.; Andreassen, Ole A.; Wang, Lei; Pearlson, Godfrey D.; et al.
Highlights: We examined the previously identified association of reduced gray matter concentration in the insula - medial prefrontal cortex and a quantitative trait locus located in 12q24 in a SZ dataset. A parallel independent component analysis (pICA) was used to examine the associations in 409 individuals with schizophrenia and 421 healthy controls. The insula – mPFC gray matter component was negatively correlated with a genetic component involved in the QTL. The protein-coding genes contributing to the correlated genetic component have been implicated in psychiatric disorders, immune response, and neuroinflammation. Abstract: The direct effect of genetic variations on clinical phenotypes within schizophrenia (SZ) remains elusive. We examined the previously identified association of reduced gray matter concentration in the insula - medial prefrontal cortex and a quantitative trait locus located in 12q24 in a SZ dataset. The main analysis was performed on 1461 SNPs and 830 participants. The highest contributing SNPs were localized in five genes including TMEM119, which encodes a microglial marker, that is associated with neuroinflammation and Alzheimer's disease. The gene set in 12q4 may partially explain brain alterations in SZ, but they may also relate to other psychiatric and developmental disorders.